Molecular characterization of allelic variants of (GATA) n microsatellite loci in parthenogenetic lizards Darevskia unisexualis (Lacertidae) - Korchagin, V.I.; Badaeva, T.N.; Tokarskaya, O.N.; Martirosyan, I.A.; Darevsky, I.S.; Ryskov, A.P. (Gene, 2007)
Populations of parthenogenetic lizards of the genus Darevskia consist of genetically identical animals, and represent a unique model for studying the molecular mechanisms underlying the variability and evolution of hypervariable DNA repeats. As unisexual lineages, parthenogenetic lizards are characterized by some level of genetic diversity at microsatellite loci. We cloned and sequenced a number of (GATA) n microsatellite loci of Darevskia unisexualis. PCR products from these loci were also sequenced and the degree of intraspecific polymorphism was assessed. Among the five (GATA) n loci analysed, two (Du215 and Du281) were polymorphic. Cross-species analysis of Du215 and Du281 indicate that the priming sites at the D. unisexualis loci are conserved in the bisexual parental species, D. raddei and D. valentini. Sequencing the PCR products amplified from Du215 and Du281 and from monomorphic Du323 showed that allelic differences at the polymorphic loci are caused by microsatellite mutations and by point mutations in the flanking regions. The haplotypes identified among the allelic variants of Du281 and among its orthologues in the parental species provide new evidence of the cross-species origin of D. unisexualis. To our knowledge, these data are the first to characterize the nucleotide sequences of allelic variants at microsatellite loci within parthenogenetic vertebrate animals.